From waste to resource: Transforming used tires into crumb rubber for economic growth - Heru Agus Santoso; Dewa Kusuma Wijaya; Nur Islahudin; Herwin Suprijono (Community Empowerment, 2025)
The increasing number of motorized vehicles in Indonesia has resulted in the accumulation of used tire waste, which is difficult to recycle or decompose. Crumb rubber, as a recycled product made from used tire waste, has great potential for use in various innovative applications. This activity program is partnered with the Repro UMKM group located in Nongko Lanang Hamlet, Wonolopo, Mijen District, Semarang City. The purpose of this community service is to implement innovative technology for processing used tire waste into crumb rubber as an industrial raw material for making high-quality products. The implementation of this program includes the fabrication of machines for crumb rubber production and providing technological education about the operation of the machines to the partners. Through this activity, partners are given the knowledge and skills needed to run the production process. The results of implementing crumb rubber technology provide significant benefits in terms of the economy, environment, and society. Economically, recycling used tire waste produces crumb rubber, which can increase partner income, with a market price of around IDR 65,000/kg. From an environmental perspective, crumb rubber offers a solution to the problem of used tire waste, reducing long-term negative impacts. On the social aspect, crumb rubber production activities create new jobs for business actors and communities that contribute to the provision of used tire waste.